EFEKTIVITAS PENYELENGGARAAN ADMINISTRASI DESA DI DESA MOLOBOG KECAMATAN MOTONGKAT KABUPATEN BOLAANG MONGONDOW TIMUR - MOKODOMPIT, YUMI; TAMPI, GUSTAAF BUDDY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2019)
The aim of the research was to explain the effectiveness of village administration in Molobog village ofMotomgkad district of East Bolaang Mongondow. The study uses qualitative approach methods. Theinformant is one person as the head of the village, four as a village officer/device, and four people as awhole society as much as 9 Informans. Data collection using interview guidelines, while the analyticaltechniques used are interactive model analyses of Miles and Hubernan. Based on the results of analysis ofdata drawn conclusions: The aim of this research is to explain the effectiveness of village administration inMolobog village of Motomgkad district of East Bolaang Mongondow. Based on the results of the researchthat has been done by the author, it can be concluded as follows: (1) Production or realization of programsand government activities of Molobog village of Motomgkad regency of East Bolaang Mongondow Whichis planned or about the work of the government of Molobog villages Motomgkad district of East BolaangMongondow in administration is already very good. According to the work or task given with the ability ofthe village government employees in the administrative administration with guidance on the regulation orregulation of government that has been established and administrative guidelines. (2) The efficiency oraccuracy of the use of organizational resources, especially human resources and the cost in achieving therealization of the program and activities Pemerinah the village that has been planned/determined alreadyshowed excellent timeliness this is facilitated Because of the innovations that the village government has.(3) Adaptation or flexibility in this case the ability of the village government in response to the developmentof tasks/employment or in the face/handling of issues that arise already good. The ability to adapt the villagegovernment apparatus with the working environment and good organization to produce a workingrelationship between the employer and co-workers as well as attitudes and relationships to the recipientcommunity is very well established service.Keywords: Effectiveness, implementation of village administration